2021
DOI: 10.3390/photonics8100426
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Defect Evaluation of Mono-Like Cast Silicon Wafers

Abstract: Solar cells based on mono-like cast silicon (MLC-Si) have been attracting increasing attention in the photovoltaic (PV) market due to their high energy conversion efficiency and low cost. As in the production of monocrystalline silicon (MC-Si) and polycrystalline silicon (PC-Si) cells, various defects will inevitably occur during the production process of MLC-Si cells. Although computer vision technology has been employed for defect detection in the production processes, it is still difficult to achieve high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Experiment results showed that the applied CNN network system outperformed the other two applied networks. Jianbo Yu [9] implemented enhanced stacked denoising autoencoder (ESDAE) on wafer dataset (WM-811K) for wafer map pattern recognition. The proposed method was compared with commonly used recognizers like SVM, BPN and DPN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiment results showed that the applied CNN network system outperformed the other two applied networks. Jianbo Yu [9] implemented enhanced stacked denoising autoencoder (ESDAE) on wafer dataset (WM-811K) for wafer map pattern recognition. The proposed method was compared with commonly used recognizers like SVM, BPN and DPN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the use of computer vision in detecting defects in railway tracks has already been studied [16,17]. Machine learning methods have been successfully applied in order to detect and monitor surface defects of photovoltaic panels (PV) [18,19]. The improved MobilenetV1-YOLOv4 network has been successfully used to detect insulation defects and thereby improve the security of power lines [20].…”
Section: Introductionmentioning
confidence: 99%